VARIABEL SOSIAL SEBAGAI PENENTU PENGGUNAAN MAKIAN DALAM BAHASA INDONESIA - Mahmud Fasya; Euis Nicky Marnianti Suhendar (Linguistik Indonesia, 2013)
This study was driven by the phenomenon of the use of swear words that has increasingly been practiced in Indonesian. It was aimed to describe the influence of social classes, gender, and the age of the speakers on the use of swear words. The findings revealed that the sociolinguistic variables, which include (1) social classes, consisting of educational level and type of work, (2) sex, and (3) age of the speakers, profoundly influenced the use of swear words in Indonesian, both in the use of linguistic forms and their references. Thus, the use of swear words in Indonesian can indicate the characteristics and background of the speakers.